The construction technology and simulation analysis of a cable-stayed arch composite bridge. Issue 1 (June 2021) - Chen, Zhou; Xu, Haocheng; Lu, Hanwen; Chen, Zepeng; Lin, Hongxin; Wu, Xi
Abstract: In order to explore the changes of mechanical properties of cable-stayed arch composite bridge in different construction stages, this paper takes a 136m tensed-string arch bridge as the engineering background, briefly describes the construction steps of grid lifting, and adopts Madis/Civil finite element analysis software for modeling. The actual construction process of the arch bridge is simulated by classifying different construction stages. The static and dynamic mechanical properties and stability of arch Bridges are studied. Through research and analysis, the main conclusions are drawn that the cables of the tensioned arch bridge bear part of the load of the original arch rib and girder.